Application of vacuum-instillation laparostomy in gunshot abdominal wounds - P. N. Romashchenko; A. A. Sazonov; N. A. Maistrenko; I. A. Makarov; R. K. Aliev; V. V. Semenov; D. S. Krivolapov (Вестник хирургии имени И.И. Грекова)
Penetrating abdominal wounds occupy a significant place in the structure of gunshot injuries in peacetime and war. They are usually characterized by extensive multiorgan damage with the development of peritonitis, the course of which largely determines the outcome of treatment. Therefore, the main task in providing specialized surgical care for victims with gunshot abdominal wounds is to relieve peritonitis in order to prevent the generalization of the septic process. One of the modern trends in solving this problem is vacuum-assisted laparostomy. However, data on its use are presented in rare publications and are usually based on small samples of patients with secondary peritonitis. At the same time, we did not find any information in the available sources about the effectiveness of the most promising modification of this technique – vacuum-instillation laparostomy for gunshot abdominal wounds. This article demonstrates the first experience of the successful use of vacuum-instillation laparostomy in a patient with gunshot abdominal wound complicated by abdominal sepsis. The obtained results indicate the high potential of using this technique in this difficult category of patients.